An assessment of time integration schemes for dynamic geotechnical problems - Kontoe,S; Zdravkovic,L; Potts,DM (Computers and Geotechnics, 2007)
The performance of the generalized-α, Newmark, HHT and WBZ time integration schemes is examined for a boundary value problem of a deep foundation subjected to various earthquake loadings. The effects of the frequency content of the earthquake excitation and the natural frequency of the numerical model on the performance of the above-mentioned algorithms are considered. The various time integration methods are compared in terms of accuracy, the ability to control high-frequency dissipation and run time. It is concluded from the finite element analysis results that the generalized-α scheme has superior qualities compared to the other algorithms investigated.